Strengthening of Reinforced Concrete Beams Weak in Shear Using GFRP - Shaik, Qudhan; Polu Raju, P (International Journal of Engineering and Technology, 2018)
Due to lateral forces acting on the structure, stresses are generated in the beam which causes beam failure. To overcome those stresses in the existing structures, retrofitting is one of the techniques to increase the lateral strength. In this study, an experimental investigation was done on RC beams to check the shear behavior by comparing control RC beams with strengthened RC beams. To observe the shear behavior considered RC Beams were made weak in shear and then Retrofitted. Two sets of beams were considered, out of which, set-1 consists of three control specimens with shear reinforcement of 100%, 50%, and 30%. Set-2 consists of three retrofitted specimens with GFRP Strips with shear reinforcement of 100%, 50%, and 30%. GFRP strips were provided around the beam with different spacing. The results concluded that the retrofitted specimens have more load carrying capacity compared to control specimens. Thus, the retrofitting is a feasible solution to overcome the stresses developed in the structure. The study also involves the behavior of shear having several GFRP layers and orientation of ultimate load carrying capacity, failure mode and crack pattern of the beam are also investigated.Â Â